Klausul Arbitrase dan Kewenangan Absolut Lembaga Arbitrase dalam Praktek Penyelesaian Sengketa di Luar Pengadilan - Syamana, Femmy; Aidi, Zil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In Indonesia, the settlement of disputes through arbitration is regulated by Law no. 30 of 1999 concerning Arbitration and Alternative Problem Resolutions. Article 7 Law no. 30 of 1999 stipulates that the parties can agree to an agreement on a dispute that has occurred or will occur between them to be resolved through arbitration with a written agreement agreed upon by the parties. In the selection of arbitral settlement there is a link between the arbitration clause and the selection of settlement through arbitration as well as the implementation of absolute authority and the selection of arbitral institutions in the practice of dispute resolution outside the court. The approach method used is normative juridical. The results of the study state that the choice of arbitration as a dispute resolution is based on a contract in accordance with what is implied in Article 7 and Article 9 paragraph (1) of Law Number 30 of 1999, and in this case the parties to the agreement agree to include an arbitration clause, The court is bound by the agreement made by the parties, with the provisions of the article, the absolute competence of arbitration is born when the parties expressly choose to resolve disputes through an arbitration forum where this has been accommodated in Article 3, Article 4, Article 10 and Article 11 paragraphs (1) and (2) in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, which negates the authority of court institutions to examine cases that are already bound by an arbitration clause.